Black leaf streak disease and plantain fruit characteristics as affected by tree density and biomass management in a tropical agroforestry system - Norgrove, L.; Hauser, S. (Springer, 2013)
Black leaf streak disease (BLSD) affects both bananas and plantains. Anecdotal evidence suggests that when plantain is grown under shade in agroforestry systems, there is less damage from BLSD. In this study, BLSD severity and agronomic fruit characteristics of plantain were compared under high and low timber stand densities (TSD), and also under different crop management systems (mulching, burning, intercropping). By 11 months after planting, in high TSDs, plants had 1.2 more standing leaves, 1.5 more symptom-free leaves and a lower percentage of total leaf area attacked than in low TSDs. At harvest, plants in high TSDs had, on average, 1.4 more standing leaves than those in low TSDs. Percentage leaf area attacked by BLSD was 43.0 % in high TSD treatments, significantly lower than the 57.2 % in low TSD treatments. There was a significant and positive relationship between the number of leaves at flowering and dry fruit bunch mass for plantains grown under low TSD. However, there was no correlation between the number of leaves and fruit mass for the high TSD. The beneficial effects of shade in the high TSD, such as reduced severity of BLSD, were established. However, as there was bunch mass loss associated with reduced leaf production rates under the high TSD, a reduction in BLSD only partially compensated for this yield loss. Thus overall, at the high TSD, there was no yield gain from reduced BLSD.